Maintenance audits handbook a performance measurement framework - Pascual, Diego Galar; Kumar, Uday (CRC Press, Taylor & Francis Group, 2016)
Maintenance Audits Handbook: A Performance Measurement Framework explores the maintenance function and performance of an organization, and outlines the key aspects required for an effective and efficient maintenance performance measurement (MPM) system. Incorporating different aspects of traditional literature and considering various frameworks on the subject, it examines the auditing process as well as the use and development of maintenance metrics. It identifies different frameworks and models showcasing how MPM systems should be implemented as well as the values that are created when different frameworks are used.